2018
DOI: 10.1029/2018gl077555
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Hess Deep Rift at the Galapagos Triple Junction

Abstract: At the Galapagos triple junction, the westward propagating Cocos-Nazca (C-N) Rift breaks intõ 0.5 Ma crust accreted at the East Pacific Rise. Rifting transitions to full magmatic seafloor spreading in the wake of the propagating tip. The 25-km-long Hess Deep rift is the transitional segment from rifting to spreading. Intrarift ridge (IRR), located within Hess Deep rift, is interpreted as a detachment fault, which exhumes deep-seated rocks to the seafloor. Although transitional segments must have occurred throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 72 publications
(116 reference statements)
1
18
0
Order By: Relevance
“…Since these early tectonic studies, the western end of the Galapagos gore has been the focus of numerous efforts, including Ocean Drilling Project (ODP) Leg 147 and Integrated Ocean Drilling Program (IODP) Leg 345, which drilled the Intrarift Ridge (IRR) in Hess Deep rift (e.g., Ferrini et al, 2013;Francheteau et al, 1990;Gillis et al, 1993Gillis et al, , 2014Karson et al, 2002;MacLeod et al, 1996;Stewart et al, 2003). The IRR has been interpreted as a south facing, low-angle, long-lived normal fault (i.e., detachment fault) (e.g., Ballu et al, 1999;Francheteau et al, 1990;Lonsdale, 1988;Smith & Schouten, 2018;Wiggins et al, 1996), and studies have been conducted primarily to explore the geochemistry and architecture of the crust and upper mantle exposed at the seafloor. Near-axis values decrease toward the east and become more centered under the axis.…”
Section: 1029/2020gc008957mentioning
confidence: 99%
See 3 more Smart Citations
“…Since these early tectonic studies, the western end of the Galapagos gore has been the focus of numerous efforts, including Ocean Drilling Project (ODP) Leg 147 and Integrated Ocean Drilling Program (IODP) Leg 345, which drilled the Intrarift Ridge (IRR) in Hess Deep rift (e.g., Ferrini et al, 2013;Francheteau et al, 1990;Gillis et al, 1993Gillis et al, , 2014Karson et al, 2002;MacLeod et al, 1996;Stewart et al, 2003). The IRR has been interpreted as a south facing, low-angle, long-lived normal fault (i.e., detachment fault) (e.g., Ballu et al, 1999;Francheteau et al, 1990;Lonsdale, 1988;Smith & Schouten, 2018;Wiggins et al, 1996), and studies have been conducted primarily to explore the geochemistry and architecture of the crust and upper mantle exposed at the seafloor. Near-axis values decrease toward the east and become more centered under the axis.…”
Section: 1029/2020gc008957mentioning
confidence: 99%
“…Near-axis values decrease toward the east and become more centered under the axis. Smith and Schouten (2018) examined the three initial rift basins developing in the Galapagos gore and suggested that the basin identified by Searle and Francheteau (1986) west of Hess Deep rift represents the earliest stage of rifting (s1, Figure 2a). The next segment to the east, the 24-km-long Hess Deep rift (s2), was identified as a transitional segment from rifting to magmatic seafloor spreading, displaying the growth of an axial volcanic ridge (AVR) in its eastern section and flanked on the north by an active low-angle detachment fault (the IRR).…”
Section: 1029/2020gc008957mentioning
confidence: 99%
See 2 more Smart Citations
“…IODP Expedition 345 32 , 33 drilled several holes towards the base of a ~3 km south-facing fault scarp exposing lower crustal gabbros and upper mantle rocks with an age of 1.27–1.42 Ma 34 . This fault has recently been interpreted as a detachment fault 35 . Three holes at IODP Site U1415 recovered intact sections of layered gabbro including gabbronorite, olivine gabbro and significant intervals of troctolite containing up to 30% olivine.…”
Section: Resultsmentioning
confidence: 99%